PENERAPAN LATIHAN WALL PASS UNTUK MENINGKATKAN KEMAMPUAN PASSING FUTSAL PADA SISWA EKSTRAKURIKULER DI PONDOK PESANTREN AL-HAADI LUBUKLINGGAU - Anggra Mahdy Anzarafi; Muhammad Shudy (CV Grasta Glory, 2026)
This study aims to determine the effectiveness application of wall pass training to improve futsal passing skills in extracurricular students at the Al-Haadi Islamic boarding school in Lubuklinggau. The type of research used is a quasi-experimental method. The population used is 20 students of the Al-Haadi Islamic boarding school in Lubuklinggau. The research sample was taken from students with junior high school criteria totaling 15 students. Data collection was carried out using test techniques in the form of passing accuracy tests. Data analysis used the SPSS 23 parametric statistical formula, the t-test, namely the Paired Samples T Test. The results of the analysis obtained by the test criteria a = 0.05 and dk (n-1), then the t_table was obtained at 1.7613 and the t_count was 25,252. Because t_count ≥ t_table, Ha was accepted and Ho was rejected. The hypothesis stating that the Application of Wall Pass Training to Improve Futsal Passing Skills in Extracurricular Students at the Al-Haadi Islamic Boarding School in Lubuklinggau is accepted. Thus, wall pass training can significantly improve futsal passing skills.